Hubungan Pengetahuan dan Perilaku Pengawas Minum Obat Terhadap Kepatuhan Minum Obat Pada Pasien TB Paru Di Puskesmas Tobadak Kabupaten Mamuju Tengah - Swarjana, I Kadek Dwi; Sukartini, Tintin; Makhfudli, Makhfudli (Jurnal Keperawatan Muhammadiyah, 2021)
Objective: Indonesia is a country with the third highest TB burden in the world, after India and China. Tuberculosis is a global health problem that mostly occurs in developing countries. The cause of failure to treat pulmonary TB patients is inadequate knowledge that is caused due to low knowledge and lack of supervision carried out by the PMO. This study aims to get an overview of the relationship between the level of knowledge and behavior of supervisors taking medication to medication adherence in patients with pulmonary TB. Methods: This study used a descriptive analytic design with a cross-sectional approach. Data collection techniques are carried out by survey and observation. Sampling by purposive sampling. Results: The results of the study revealed that the statistical test using the SPSS version 16.0 program with the help of the Chi-Square test found that there was a relationship between knowledge and adherence to medication with a value of p = 0.001 with a significance level of Î± = 0.05 and PMO behavior with compliance with p values = 0.017 with a significance level of Î± = 0.05. Conclusion: The results of the study show that there is a relationship between knowledge and behavior towards medication adherence for patients with pulmonary TB